Plant Biostimulants: New Insights Into the Biological Control of Verticillium Wilt of Olive - López-Moral, Ana; Agustí-Brisach, Carlos; Trapero, Antonio (Frontiers in Plant Science, 2021)
Verticillium wilt of olive (Olea europaea subsp. europaea L.) (VWO), caused by the hemibiotrophic soil-borne fungus Verticillium dahliae Kleb., is considered the major limiting factor of this crop in Mediterranean-type climate regions of the world. The absence of effective chemical treatments makes the control of the disease difficult. In this way, the use of biostimulants and host plant defense inducers seems to be one of the most promising biological and eco-friendly alternatives to traditional control measures. Thus, the main goal of this study was to evaluate the effect of 32 products, including amino acids, micronutrients, microorganisms, substances of natural origin, copper complex-based products, and organic and inorganic salts against the disease under controlled conditions. To this end, their effects on mycelial growth and microsclerotia (MS) inhibition of V. dahliae were evaluated by means of dual cultures or by sensitivity tests in vitro as well as on disease progression in planta. Wide ranging responses to the pathogen and disease reduction levels were observed among all the products tested, suggesting multiple modes of action. Copper-based products were among the most effective for mycelial growth and MS inhibition, whereas they did not show an important effect on the reduction of disease severity in planta. Phoma sp. and Aureobasidium pullulans were the most effective in disease reduction in planta with foliar application. On the other hand, two phosphite salts, one with copper and the other with potassium, were the most effective in disease reduction in planta when they were applied by irrigation, followed by A. pullulans and Bacillus amyloliquefaciens. This study will be useful to select the best candidates for future studies, contributing significantly to new insights into the current challenge of the biological control of VWO.